2004
DOI: 10.1038/sj.mp.4001420
|View full text |Cite
|
Sign up to set email alerts
|

A major SNP haplotype of the arginine vasopressin 1B receptor protects against recurrent major depression

Abstract: Increasing amounts of data suggest that affective disorders might be related to dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, one of the stress-response systems. Arginine vasopressin (AVP) influences several symptoms, relevant to affective disorders, notable memory processes, pain sensitivity, synchronization of biological rhythms and the timing and quality of REM sleep. We examined whether genetic variations in the AVP receptor 1b gene (AVPR1b) could be associated with increased susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 24 publications
(19 reference statements)
0
51
1
Order By: Relevance
“…34,75,76 It was also of interest to find single AR nuclear and/ or cytoplasmic staining inside the PVN in the human hypothalamus ( Figure 4) as this implicates a potential role of androgens on the activity of peptidergic neurons other than CRH neurons, for example the vasopressin or oxytocin-containing neurons, both of which are also involved in central stress responses and mood disorders. [77][78][79][80][81][82] This topic also deserves further study.…”
Section: Mmtv-arementioning
confidence: 99%
“…34,75,76 It was also of interest to find single AR nuclear and/ or cytoplasmic staining inside the PVN in the human hypothalamus ( Figure 4) as this implicates a potential role of androgens on the activity of peptidergic neurons other than CRH neurons, for example the vasopressin or oxytocin-containing neurons, both of which are also involved in central stress responses and mood disorders. [77][78][79][80][81][82] This topic also deserves further study.…”
Section: Mmtv-arementioning
confidence: 99%
“…This paper is a part of a systematic evaluation of the possible role of a number of HPA axis-related genes in the genetic vulnerability for MDD. Previously, our group published reports on the genes encoding for the CRF receptor 2, the CRF binding protein, and the AVP receptor 1B (Claes et al, 2003;van West et al, 2004;Villafuerte et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Postmortem studies have found an elevated number of AVP-expressing neurons, increased AVP level in the PVN (Purba et al, 1996, Merali et al, 2006 and an enhanced AVP mRNA You created this PDF from an application that is not licensed to print to novaPDF printer (http://www.novapdf.com) in the SON (Meynen et al, 2006). Additionally, a single nucleotide polymorphism of the AVP V1b receptor has been found to protect against major depression (van West et al, 2004). Preclinical studies using the first orally active non-peptide V1b antagonist (SSR 149415) resulted in a reduction of floating in the FS test (Griebel et al, 2002).…”
mentioning
confidence: 99%